The Relationship Between Digital Transformation and Organisational Agility in Public Institutions: The Case of a University - Yıldırım, Kürşad Emrah; Gemici, Eser; Yıldırım Başkan, Tuğçe (International Review of Management and Marketing, 2025)
The digital transformation experienced in recent years has caused many organizations to change their shape, update their processes, and renew themselves with new competencies and capabilities. The new order emerging with the rapid change has forced organizations to be more agile. The study was conducted to examine the relationship between digital transformation and organizational agility in public institutions, which are among the organizations affected by transformation. In particular, it was tried to examine how digital transformation affects agility in organizations through a university example. In the evaluation made through the university example, it was revealed how an agile organizational structure can be formed in an institution where digital transformation takes place and how digital transformation is related to the dimensions that constitute organizational agility. In the study, explanatory factor analysis was applied to measure the structural validity of the scales and simple regression analysis was applied to test the hypotheses. As a result, it is seen that the successful realization of digital transformation in public institutions makes organizations more agile and if this is supported by agile management approaches, the advantages that public institutions will gain will increase.